2023
DOI: 10.1101/2023.02.02.23285206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimized testing strategy for the diagnosis of GAA-FGF14ataxia

Abstract: Background Dominantly inherited GAA repeat expansions inFGF14are a common cause of spinocerebellar ataxia (GAA-FGF14ataxia; SCA27B, late-onset). Molecular confirmation ofFGF14GAA repeat expansions has thus far mostly relied on long-read sequencing, a technology that is not yet widely available in clinical laboratories. Methods We developed and validated a strategy to detectFGF14GAA repeat expansions using long-range PCR, bidirectional repeat-primed PCRs, and Sanger sequencing. We compared this strategy to targ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
3
13
0
Order By: Relevance
“…Specifically, we showed that SCA27B was particularly frequent in patients with pure cerebella ataxia. SCA27B accounted for 28% of cases in our cohort of patients with unsolved LOCA, a frequency similar to that reported in other European series [5,6,8,11,12]. Patients with SCA27B consistently presented with a slowly progressive pan-cerebellar syndrome predominantly affecting the gait, with frequent downbeat nystagmus and episodic symptoms at disease onset.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Specifically, we showed that SCA27B was particularly frequent in patients with pure cerebella ataxia. SCA27B accounted for 28% of cases in our cohort of patients with unsolved LOCA, a frequency similar to that reported in other European series [5,6,8,11,12]. Patients with SCA27B consistently presented with a slowly progressive pan-cerebellar syndrome predominantly affecting the gait, with frequent downbeat nystagmus and episodic symptoms at disease onset.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the phenotype of our patients did not differ from previous descriptions [5,6,[11][12][13][14]. Although neuropathy does not appear to be a core feature of SCA27B [5,6,8], an observation further supported by our study, hypopallaesthesia (without corresponding abnormalities on nerve conduction studies) was present in 50% of our patients. Similar findings were recently identified in a German cohort, suggesting impairment of the afferent sensory tracts [13].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…FGF14 GAA expansions were screened as reported elsewhere 13 using a three‐step procedure including fluorescent long‐range polymerase chain reaction (PCR), bidirectional repeated‐primed PCRs (RP‐PCRs), and agarose gel electrophoresis of long‐range PCR products and Sanger sequencing. The detailed procedures are described in Data S1.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental methodology was performed as described previously, 10 with a modification of the 5 0 repeat-primed PCR (RP-PCR) for cases genotyped in Athens (Suppl. methods).…”
Section: Methodsmentioning
confidence: 99%